Citrus Pathology - Gill, Harsimran; Garg, Harsh (IntechOpen, 2017)
This book is an attempt to compile different aspects of citrus pathology to provide an overall knowledge to those who are interested in it, so that they may identify the bottlenecks to improve it further. The book chapters detail about citrus diseases, metabolic changes in citrus plants against various stresses, quorum sensing and its role in symptom development, preharvest and postharvest disease management, and application of citrus and its compounds. The goal of this book is to provide the most up-to-date review on information available on pathological aspects of citrus. Therefore, this book will equip academia and industry people with adequate basic knowledge of citrus diseases and management options.